Differences in Knowledge, Attitudes, and Vaginal Hygiene Behaviors toward the Incidence of Pathological Vaginal Discharge among Female Students of the Faculty of Law and the Faculty of Economics - Rinova Dinda Amelya Lubis; Rini Syahrani Harahap (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Vaginal discharge is one of the most common reproductive health problems experienced by women and refers to vaginal fluid other than menstrual blood. In Indonesia, approximately 75% of women have experienced vaginal discharge at least once, while the prevalence among adolescent girls aged 15–24 years reaches 31.8%. Although vaginal discharge is generally physiological, poor vaginal hygiene may increase the risk of pathological vaginal discharge. This study aimed to analyze differences in knowledge, attitudes, and behaviors regarding vaginal hygiene among female students of the Faculty of Law and the Faculty of Economics at Universitas Muhammadiyah Sumatera Utara (UMSU) in relation to the occurrence of vaginal discharge. A cross-sectional design was employed using an accidental sampling technique. Data were collected through questionnaires and analyzed using the Wilcoxon Matched Pairs Test. The findings showed that good knowledge of vaginal hygiene was predominantly found among Faculty of Economics students (71.3%), whereas poor knowledge was mostly identified among Faculty of Law students (1.3%). Positive attitudes were highest among Faculty of Law students (91.3%), while good vaginal hygiene practices were more common among Faculty of Economics students (72.5%). Statistical analysis revealed significant differences in knowledge, attitudes, and behaviors related to vaginal hygiene between students of both faculties in relation to the occurrence of pathological vaginal discharge. The study concludes that differences in knowledge, attitudes, and hygiene behaviors are associated with the occurrence of pathological vaginal discharge among female students.